Metodología para la evaluación de la seguridad estructural de puentes - Bolaños-Ávila, Darnel Gerardo (Instituto Tecnológico de Costa Rica, 2018)
The objective of the present work is to show the methodology to perform a reliability analysis in a prestressed concrete girder bridge, based on deformation data obtained from a diagnostic load test. It was developed three performance indicators: reliability index, probability of failure and probability of survivor. Besides, was calculated the load rating to make a comparison between both methods in terms of safety. Both were calculated with two limit states: flexural failure and stress. The distribution function and statistical parameters of the random variables were based on the theory (since there is not physical tests for materials) and processed using the Monte Carlo simulation. The software Minitab 18® was used to the statistical analysis. The structural model of the bridge was elaborated using the software CSi Bridge 2019, based on the As-Built drawings. The results indicate that the studied bridge has an excellent condition of safety for both approaches, probabilistic and deterministic, and satisfy the international normative standars from AASHTO. Also were identified different benefits from the implementation of the diagnostic load test, for example the real behavior of the structure with the external forces.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2018.
Keywords: Confiabilidad; Diagnóstico; Puentes; AASHTO; Metodología; Research Subject Categories::TECHNOLOGY::Civil engineering and architecture